Use Of Websites And Social Media As Information Systems At Smp Muhammadiyah 9 Yogyakarta - Arifani Maulida Rahman; Yulia Luthfiyani Azizah; Abdul Hopid (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem: Not all educational institutions can maximize school websites and social media to support the continuity of education as a reliable media system in the digital era. Because of the critical role of the press in educational institutions, this article will describe the types and uses of social media and websites in educational institutions, especially at SMP Muhammadiyah 9 Yogyakarta. Purpose: this article will describe the types and uses of social media and websites in educational institutions, especially at SMP Muhammadiyah 9 Yogyakarta. Design/methods/approach: The method used in this research is a descriptive qualitative method—collecting data using interviews from two summers (1 employee and one teacher), observation, and documentation. The data analysis techniques in this study are; data collection, data reduction, data display, and conclusion. Findings: The findings of this study are; SMP Muhammadiyah 9 has several media systems; website, Instagram, Facebook, and youtube. However, the media is not managed properly and optimally, and it is evident that the school does not regularly update the system. Even if it is done, it will make a significant contribution to the progress of the school.